Amyand's Hernia in a Neonate Presenting with Inguinoscrotal Erythema: A Difficult Diagnosis - Mohamed, Ahmed; Fagelnor, Anas (European Journal of Pediatric Surgery Reports, 2019)
The presence of the vermiform appendix, whether inflamed or not, inside a hernial sac is known as Amyand's hernia. Due to nonspecific signs, preoperative diagnosis is not common and requires a high index of suspicion along with awareness of this rare entity. It is more commonly mistaken for a strangulated or incarcerated inguinal hernia. Most cases of reported Amyand's hernia with appendicitis were in pre-term babies, infants, and post-menopausal women. We present a similar case in a 19-day-old, full-term baby presenting with inguinoscrotal edema, erythema, and without a palpable inguinoscrotal mass.
Keywords: Amyand's; appendicitis; inguinal hernia; neonate